Status of crabbers in northern Catanduanes, Philippines, and their perspectives on national policies and plans for the blue swimming crab - Recie B. Bonaos; Maria Mojena Gonzales-Plasus (Marine and Fishery Sciences)
Marine resources in the Philippines are rapidly declining due to overfishing and habitat degradation, threatening biodiversity and the livelihoods of coastal communities and small-scale fishers. Crustaceans, like the blue swimming crab (Portunus pelagicus), which serve as a vital source of income for small-scale fishers, are among the most affected. To combat the depletion of fishery resources, the Philippine government implemented the National Blue Swimming Crab Policies and Plans (NBSCPP). This study focused on the perspectives of crabbers in northern Catanduanes to provide insights into the implementation and impact of the NBSCPP at the community level. Data were collected through interviews with 208 crabbers using a modified survey questionnaire based on the NBSCPP framework. Results revealed that the income of crabbers and their families fell significantly below the poverty threshold, a challenge further compounded by low levels of formal education, which limited their opportunities for alternative livelihoods. Crabbers demonstrated a general awareness of conservation and management policies, particularly on closed fishing seasons and size limits, and exhibited a positive attitude toward compliance and participation in conservation initiatives. However, socio-demographic characteristics such as education and income were not significantly associated with crabbers’ awareness or attitudes toward policy implementation. To enhance awareness and foster sustainable practices, the study recommended intensified information, education, and communication campaigns, stricter enforcement of regulations, and the development of alternative livelihood programs. These measures are critical to ensuring the long-term sustainability of the blue swimming crab population and supporting the livelihoods of communities in northern Catanduanes.